Peran Pendidikan Kewarganegaraan Dalam Menanamkan Nilai–Nilai Kebangsaan Pada Generasi Muda Di Era Globalisasi - If Ser Itoloni Waruwu; Firman Syah Putra Waruwu; Darwis Triadi Telaumbanua; Hendrikus Otniel Nasozaro Harefa (Jurnal Ilmu Pendidikan Pancasila, Kewarganegaraan, dan Hukum, 2025)
In the era of globalization and rapid development of information technology, challenges to national values and national identity are increasingly complex. The younger generation is faced with various foreign cultural influences that can affect their understanding and appreciation of the noble values of the nation. Therefore, Civic Education plays a role as a fortress in maintaining and instilling these values from an early age. As stated by Parawangsa, Dewi, and Furnamasari (2021), Civics Education in Primary Schools focuses on the formation of smart, skilled, and characterized citizens in accordance with Pancasila and the 1945 Constitution. In addition, civic education not only functions as a transfer of knowledge about the political and legal system, but also as a means of shaping the character and morals of students. This is in line with the view that Civics Education aims to foster and increase citizen participation in political and community life, both at the local and national levels.